Patterns, dynamics and influencing factors of Disclosure of HIV status among women and men living with HIV in Cape Town, South Africa - Austin, Evelyn (Department of Public Health and Family Medicine, 2015)
The aim of this study was to explore and examine the patterns, dynamics and influencing factors of HIV status disclosure among men and women at ARV clinics in low-income area clinics in Cape Town, South Africa and highlight areas for intervention and counselling improvement. The specific objectives were to: * Understand the factors that are associated with disclosure * Explore factors that constrain/promote disclosure of HIV status * Explore who people disclose to and why? * Investigate what impact positive/negative reactions may have had on one's health and hopefulness of living with the virus. * Make recommendations on how to address disclosure in support and treatment programs for people living with HIV. This is a sub-study of a larger study to determine the effectiveness of reproductive health interventions in 4 clinics in Cape Town. This sub-study makes use of the first two sets of interviews out of a total of 3. This was a cohort study design with structured interviews and patient exit interviews. Data were collected between September 2007 and December 2008 in the four clinics. Ethics approval was granted by the Health Sciences Faculty Research Ethics Committee - REC REF: 429/2006. Given the constantly changing nature of HIV in South Africa, tracking changes in the dynamics of disclosure over time is important, rather than relying on 'snapshot' perspectives. Analysis was fore grounded in global and Sub-Saharan African trends to draw out specificities from the South African context. The study concluded by highlighting gaps for further research and practical implications for the future of HIV prevention, support, care and treatment programming.